2001
DOI: 10.1038/35101544
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the interaction of antibiotics with the peptidyl transferase centre in eubacteria

Abstract: Ribosomes, the site of protein synthesis, are a major target for natural and synthetic antibiotics. Detailed knowledge of antibiotic binding sites is central to understanding the mechanisms of drug action. Conversely, drugs are excellent tools for studying the ribosome function. To elucidate the structural basis of ribosome-antibiotic interactions, we determined the high-resolution X-ray structures of the 50S ribosomal subunit of the eubacterium Deinococcus radiodurans, complexed with the clinically relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

47
918
5
21

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 973 publications
(991 citation statements)
references
References 47 publications
47
918
5
21
Order By: Relevance
“…A number of co‐crystal structures of macrolides bound to the ribosome have been published and they show that the main component in the binding pocket is A2058Ec 54, 55, 56. Key interactions include polar contacts between the functional groups of the C5 desosamine sugar and residues A2058Ec and A2059Ec, as well as hydrogen bonds between the three lactone hydroxy groups and the 50S ribosomal subunit (Figure 10).…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…A number of co‐crystal structures of macrolides bound to the ribosome have been published and they show that the main component in the binding pocket is A2058Ec 54, 55, 56. Key interactions include polar contacts between the functional groups of the C5 desosamine sugar and residues A2058Ec and A2059Ec, as well as hydrogen bonds between the three lactone hydroxy groups and the 50S ribosomal subunit (Figure 10).…”
Section: Protein Synthesis Inhibitorsmentioning
confidence: 99%
“…11 Accordingly, we hoped that a prolonged anchor group at the C-4 00 position might increase the affinity for the new binding sites of the nucleotides in the peptide tunnel, further enhancing antibacterial activity against resistant strains. On the basis of the result Antibacterial activities of 4 00 -O-carbamate derivatives C Ma et al of the high-resolution X-ray co-crystal structure study, 11,19 which showed the overlapping of the macrolide binding structure with clindamycin and chloramphenicol, we designed a series of novel 15-membered AZM derivatives with the C-4 00 prolonged side chains, the length of which was eight or nine atoms distant from oxygen atom at the C-4 00 position to the aromatic ring. These compounds with prolonged side chains showed remarkably improved activity against strains encoded by the erm gene or the erm and mef genes, compared with the corresponding compounds with the C-4 00 short arylalkyl side chain reported by previously by us.…”
Section: Discussionmentioning
confidence: 99%
“…8 This results in tighter binding to ribosomes and imparts some activity against methylated ribosomes in some species. 9,10 The study of the high-resolution X-ray co-crystal structures has revealed that macrolides bind at the entrance to the peptide tunnel in the 23S rRNA, and the cladinose group in their structures is located at and fits with the cavity formed by G2505, C2610 and C2611 in domain V. 11 On the basis of the results of the X-ray co-crystal structure study, many new derivatives of macrolides for the effective management of erythromycin resistance have been investigated by different research groups. 12 These investigations have led to the discovery of 4 00 -modified macrolide derivatives such as CP-544372 13 and A-60565 14 ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrolide antibiotics, represented by erythromycin A (ERY, 2) and its structural homologues, specifically bind to the bacterial 50S ribosomal subunit resulting in the inhibition of bacterial protein biosynthesis [2]. CLA (1) is also commonly used to target gastric Helicobacter pylori, which is implicated in both gastric ulcers and cancer [3].…”
Section: Introductionmentioning
confidence: 99%